Evaluation of Phytochemical and Production Potential of Borage (Borago officinalis L.) During the Growth Cycle - H Naghdi Badi; A Soroshzadeh; Sh Rezazadeh; M Sharifi; A Ghalavand; A Rezai (Institue of Medicinal Plants, ACECR, 2008)
Background: Borage (Borago officinalis L.) is a valuable medicinal plant with a high content of gamma linolenic acid. It has an important place in Iranian traditional medicine. Although the aerial parts of this plant are extensively used in treatment of diseases, detailed knowledge of the active constituent changes in these parts is not readily available. In addition the most data that has been reported are about oil seed of borage and its properties.   Objective: Thus, the study about changes in chemical composition/secondary metabolites at different growth stages is necessary.   Method: For this reason, in the present research the chemical composition including total phenol, total alkaloids, mucilage, total ash, acid-insoluble ash and tannins of the aerial parts were evaluated during different growth stages of borage.   Results: Results indicated that at each corresponding stage of development, starting from seedling stage until flowering stage the chemical compositions of borage aerial parts hadnchr('39')t significantly differences. Only, there were significant differences (p<0.01) in the total ash and acid-insoluble ash and these two parameters were significantly increased with the development of plants, from seedling until flowering stage. In general, at all stage, the aerial parts showed similar quality in respect of chemical compositions. Conclusion: Therefore the best harvesting time of the aerial parts is the flowering stage, because we achieved the highest fresh and dry weight at this stage.